Persepsi Pengguna Google Maps Tentang Destinasi Wisata Pantai Batukaras Pangandaran - Atef Fahrudin; Rachmaniar Rachmaniar (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Batukaras Beach in Cijulang Subdistrict, Pangandaran Regency, is an increasingly popular coastal tourism destination that has accumulated an extensive digital footprint in the form of user reviews on Google Maps, with an average rating of 4.6 out of 5 based on 1,587 reviews. This study aims to describe Google Maps users’ perceptions of Batukaras Beach through quantitative content analysis of publicly available review content. A descriptive quantitative approach was employed with a population of 1,587 reviews; through scraping using the Thunderbit tool, 223 reviews were obtained, and the sample size was calculated using the Slovin formula with a 7 percent margin of error, yielding 181 reviews selected through simple random sampling. Data were analyzed descriptively, covering the distribution of star ratings, sentiment classification, and keyword-lexicon-based thematic coding. The results show that review sentiment is dominated by positive perceptions (91.2%), followed by neutral (6.1%) and negative (2.8%). The most frequently raised themes were natural attractiveness and scenery (61.3%), comfort and safety (37.6%), tourism activities (33.1%), facilities and cleanliness (32.0%), accessibility and location (21.0%), price and cost (9.4%), and hospitality and service (7.7%). These findings confirm that Google Maps reviews can serve as a relevant source of destination-image data for tourism managers and local government in formulating tourism marketing communication strategies for Batukaras Beach.